Business Resilience Amidst The Covid-19 Pandemic - Hardana, Ali; Hararap, Naruddin Khalil; Nasution, Jafar; Damisa, Arti (Jurnal Ekonomi dan Perbankan Syariah, 2024)
The Covid-19 pandemic has an impact on various sectors of life, not only the health sector, the economic and business sectors are also experiencing a serious impact. At this time, many business actors experience various problems such as declining sales, lack of capital, hampered sales distribution and difficulties in raw materials. Therefore, a resilience is needed in order to continue to run in the midst of this difficult situation. The object of this research is UD. salacca. This research method is using a qualitative approach and then analyzed using SWOT analysis. The results of this study indicate that the results obtained from the SWOT matrix table, there are several alternative strategies for UD. Salacca to survive in the midst of the Covid-19 pandemic: (a) Alternative strategies for SO to maximize the use of digital technology to market processed salak products more widely which have guaranteed halalness, maintain cooperative relationships with distributors so that they have the opportunity to expand distribution networks outside the city and abroad, utilize social media to promote the location of business locations to attract customers and utilize digital technology to improve HR skills for the better. (b) Alternative ST strategy to reduce the number of employees so that UD. Salacca was able to survive because of the social distancing policy in the midst of the Covid-19 pandemic, declining market demand, so it had to reduce the amount of production and increase cooperation with suppliers of raw materials in order to increase the amount of production. (c) Alternative WO strategies utilize technological developments to make bookkeeping using a computer system and increase the use of technology and information to expand market share. (d) The alternative WT strategy is to utilize digital technology to increase sales turnover and utilize technology and information to establish communication with salak suppliers from various regions in order to continue to produce salak processed products.